Magnetized plasma in strong electric field: from parametric turbulence to enhanced confinement - Mikhailenko, V.S.; Mikhailenko, V.V. (Вопросы атомной науки и техники, 2013)
This report is devoted to the unified kinetic approach to the theory of parametric turbulence and to the theory of plasma turbulence in strong shear flow across the confined magnetic field. The key point in that theory is the usage of the spatial and velocity variables which are co-moving with plasma particles in magnetic and strong electric field. Статья посвящена единому подходу к кинетической теории параметрической турбулентности и к теории турбулентности сильного сдвигового течения плазмы поперек удерживаемого магнитного поля. Ключевым моментом в этой теории является использование как скоростей, так и пространственных координат, определенных в системе координат, движущейся вместе с частицами в магнитном и электрическом полях. Стаття присвячена єдиному підходу до кінетичної теорії параметричної турбулентності та до теорії турбулентності потужної зсувної течії плазми поперек утримуваного магнітного поля. Ключовим моментом у цій теорії є використання як швидкостей, так і просторових координат, визначених у системі координат, що рухається разом з частинками у магнітному та електричному полях.